Teacher Preparedness for Medical Emergencies in Belgian Classrooms: Studying Objective and Subjective First-Aid Knowledge - Maya Vermonden; Liesse Dehaerne; Jaan Toelen; David De Coninck (MDPI AG, 2023)
About one in seven accidents involving children occurs at school. Roughly 70% of these accidents involve children under the age of 12 years. Thus, primary school teachers may be confronted with accidents where first aid could improve the outcome. Despite the importance of first-aid knowledge among teachers, little is known about this topic. To fill this gap, we conducted case-based survey research on the objective and subjective first-aid knowledge of primary school and kindergarten teachers in Flanders, Belgium. An online survey was distributed to primary school and kindergarten teachers. It included 14 hypothetical first-aid scenarios in a primary school context to assess objective knowledge, along with one item to assess subjective knowledge. A total of 361 primary school and kindergarten teachers completed the questionnaire. The participants achieved an average knowledge score of 66%. Those who had completed a first-aid course had significantly higher scores. Knowledge regarding child CPR was amongst the lowest, with only 40% correct answers. Structural equation modeling showed that only previous first-aid training, recent experience with first aid, and subjective first-aid knowledge were linked to teachers' objective first-aid knowledge-particularly for basic first aid. This study shows that completing a first-aid course and completing a refresher course can predict objective first-aid knowledge. We therefore recommend that first-aid training and regular refresher courses should be mandatory in teacher training, given that a large share of teachers may need to apply first aid to a pupil at some point during their career.